Konstytucja a członkostwo Wspólnoty I Unii Europejskiej - Lasok, Dominik (Wydział Prawa i Administracji UAM, 1995)
Since Poland aspires to the membership of the European Union it seems desirable to consider the project of the new Constitution from that point of view. The Treaties which have established the Communities imply the capacity of the applicant State to enter into and to comply with the obligations arising from the membership, which is relevant to the définition of national sovereignty. The new Constitution onght to contain provisions concerning the participation in the decission- making process of the Community, the relationship between Polish law and Community law as well as procedural aspects of the exercise of the judicial function and the enforcement of decisions and judgments of Community authorities. Co-ordination of economic policies will require adaptation of the economic system to the market economy as well as of social laws in conformity with the Community system. In conclusion, the new Constitution should be based on well formulated general principles taking also into consideration the achievements of the European integration.
Constitution and membership of the European Union